2016
DOI: 10.1073/pnas.1523667113
|View full text |Cite
|
Sign up to set email alerts
|

Low-latitude arc–continent collision as a driver for global cooling

Abstract: New constraints on the tectonic evolution of the Neo-Tethys Ocean indicate that at ∼90-70 Ma and at ∼50-40 Ma, vast quantities of mafic and ultramafic rocks were emplaced at low latitude onto continental crust within the tropical humid belt. These emplacement events correspond temporally with, and are potential agents for, the global climatic cooling events that terminated the Cretaceous Thermal Maximum and the Early Eocene Climatic Optimum. We model the temporal effects of CO 2 drawdown from the atmosphere du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 70 publications
(69 reference statements)
3
81
0
Order By: Relevance
“…This progressive decrease in Sr flux from radiogenic continental areas combined with the increase in mid-oceanic ridge magmatism associated with the Tethys opening might explain the lower ( 87 Sr/ 86 Sr) seawater values during the Permian period ( 57 ). Changes in the isotopic signature of the Sr flux exported from continents are associated with the uplift of metamorphic rocks, ophiolites, and LIPs ( 22 ) can also play a significant role in the Sr isotope budget ( 56 ). The rapid weathering of these isotopically distinct rocks in favorable paleogeographic or tectonic configuration likely contributes to some of the ( 87 Sr/ 86 Sr) seawater variations over the last 1000 My (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This progressive decrease in Sr flux from radiogenic continental areas combined with the increase in mid-oceanic ridge magmatism associated with the Tethys opening might explain the lower ( 87 Sr/ 86 Sr) seawater values during the Permian period ( 57 ). Changes in the isotopic signature of the Sr flux exported from continents are associated with the uplift of metamorphic rocks, ophiolites, and LIPs ( 22 ) can also play a significant role in the Sr isotope budget ( 56 ). The rapid weathering of these isotopically distinct rocks in favorable paleogeographic or tectonic configuration likely contributes to some of the ( 87 Sr/ 86 Sr) seawater variations over the last 1000 My (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are likely to be greater than those caused by changes in the global average runoff given that spatially runoff varies substantially. Indeed, previous studies have suggested that changes in global silicate weathering fluxes could be driven by the interaction of continental configuration and sea level with the overlying runoff distribution, as determined by atmospheric circulation, over both short (10 3 -10 5 yr) and long (>10 6 yr) timescales (e.g., Gibbs and Kump, 1994;Gibbs et al, 1999;Ludwig et al, 1999;Munhoven, 2002;Donnadieu et al, 2004;Goddéris et al, 2008;Kent and Muttoni, 2008;Le Hir et al, 2009;Mills et al, 2011Mills et al, , 2013Jagoutz et al, 2016).…”
Section: Dw Weatherability and A Variable Silicate Weathering Feedbackmentioning
confidence: 99%
“…For example, basaltic catchments weather faster than other silicates and account for approximately 20-35% of the modern global silicate weathering and CO2 consumption flux, while occupying less than 5% of sub-aerial continental area (Gíslason et al, 1996(Gíslason et al, , 2009 have been critically important in controlling past levels of atmospheric CO2 (pCO2) (Li and Elderfield, 2013;Kent and Muttoni, 2013;Molnar and Cronin, 2015;Jagoutz et al, 2016). However, scaling modern observations of weathering fluxes from catchments to both large spatial and temporal scales (e.g., Wallmann, 2001;Lefebvre et al, 2013;Li and Elderfield, 2013;Kent andMuttoni, 2008, 2013;Mills et al, 2014a;Li et al, 2016;Jagoutz et al, 2016;Cox et al, 2016) remains a challenge due to the lack of phenomenological modeling frameworks that predict weathering fluxes at both catchment and global scales under different climate states.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Accumulation model, the dramatic change that characterised the reduction in CIA 15 lengths ~75 Ma included the termination of a ~3 000-km-long section of a north-dipping intra-oceanic subduction zone in the Northern Tethys ocean, corresponding to the Trans-Tethyan Subduction System (Jagoutz et al, 2016), and the cessation of subduction along the Sundaland margin (McCourt et al, 1996;Zahirovic et al, 2016) (Figs. 5c, 5d).…”
Section: Implications For Late Cretaceous To Early Palaeogene Climatementioning
confidence: 99%
“…The intra-oceanic subduction in the Neo-Tethys in our model would not be classified as a carbonate-intersecting arc due to the overriding plate (in this case largely oceanic 20 lithosphere) lacking extensive carbonate platforms. In any case, this intra-oceanic subduction zone in the Accumulation Model corresponds to the emplacement of the peri-Arabian ophiolite belt along the AfroArabian continental margin between 80-70 Ma rather than an Andean-style arc, the erosion of which has been posited as a cause of global cooling following the EECO (Jagoutz et al, 2016) (Figs. 5c, 5d).…”
Section: Implications For Late Cretaceous To Early Palaeogene Climatementioning
confidence: 99%